PERSEPSI GURU PENDIDIKAN KHUSUS TERHADAP BUKU GURU DAN BUKU SISWA DALAM KURIKULUM 2013 BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SLB - FITRIANI, YULITA (Jurnal Pendidikan Khusus, 2017)
Abstract There were teacher book and student book in curriculum 2013. The perception of special education teacher toward both books was different depending on the feeling, thinking ability, and the teacher’s experiences. Therewere two forms of perception i.e. negative and positive perceptions. This research had purposes to explain (1) the acceptation of special need teacher toward teacher book and student book in curriculum 2013 for special needs learners, (2) the comprehension of special education teacher toward teacher book and student book in curriculum 2013 for special needs learners, (3) the assessment or evaluation of special education teacher toward teacher book and student book in curriculum 2013 for special needs learners. The method used in this research was descriptive qualitative. The techniques of data collection were observation, interview, questionnaire, and documentation. The analysis step of this descriptive qualitative research involved reduction data, displaydata, and verification or concluding. The research result could be concluded (1) the acceptation of special education teacher toward teacher book and student book which behaved positive was the teacher book and student book were utilized well while behaving negative was the scientific approach could not be applied yet to special needs children, (2) the comprehension of special education teacher toward teacher book and student book which behaved positive was KD and indicator did not object the special need children who did not have cognitive hindrance, the material relation was good enough and interesting, the media needed was not too difficult, the assessment rubric helped enough, (3) the assessment of special education teacher toward teacher book and student book was distributing teacher book and student book were not maximum, there was not any signal system in teacher book and student book, there were several learning activities which were not maximally implemented yet, making RPP was more.Keywords:Perception, Special Education Teacher, TeacherBookand Student Book